Development of flipbook-based digital comics to improve learning outcomes on simple comic material - Eka Yuliani; Deni Setiawan (Universitas Muhammadiyah Malang, 2024)
According to researchers, they have made observations at SDN Purwoyoso 02 Semarang and obtained results, the problems obtained are limited learning media and student learning outcomes which are still in the low category in the content of Fine Arts lessons. This research aimed to test the effectiveness and feasibility of using Digital Comic learning media in Fine Arts subjects for class IV students at SDN Purwoyoso 02 Semarang-Central Java. The type of research used is research and development (RnD), which follows a modified Borg and Gall 9-stage model. The results of the product assessment in the form of learning media validation carried out by experts in the field of materials and media obtained an average score of 92.5% with a classification of